Angioregressive pretreatment of mature corneal blood vessels before keratoplasty: fine-needle vessel coagulation combined with anti-VEGFs - Koenig, Yanyan; Bock, Felix; Kruse, Friedrich; Stock, Klaus-Peter; Cursiefen, Claus (Cornea, 2012)
To evaluate the efficacy and safety of combined feeder vessel coagulation and topical antiangiogenic therapy using bevacizumab in the treatment of mature corneal blood vessels.Sixteen eyes of 16 patients with mature corneal neovascularization (NV) due to different underlying corneal diseases underwent fine-needle feeder vessel coagulation by diathermy and were treated postoperatively for up to 4 weeks with topical bevacizumab eye drops (containing 5 mg/mL bevacizumab) 5 times a day. Nine patients received an additional subconjunctival bevacizumab injection at the time of cautery.The mean duration of follow-up was 276 ± 147.3 days (range, 29-464 days). Regression of the feeder vessel was observed in 14 eyes. The vascularized area was reduced significantly (P < 0.05). Combined subconjunctival and eye drop antivascular endothelial growth factor treatment was significantly more effective in reducing the vascularized area compared with antivascular endothelial growth factor eye drop therapy alone (P < 0.05). Five patients (5 eyes) needed a second treatment. Thirteen patients (13 eyes) receiving topical bevacizumab treatment combined with feeder vessel coagulation showed stable visual acuity. Two patients had improved visual acuity. One patient had enlarged area of lipid keratopathy despite successful treatment of corneal NV and thus decreased visual acuity. Overall, there was a nonsignificant improvement of best-corrected visual acuity (P > 0.05).In this pilot study, fine-needle feeder vessel coagulation combined with topical bevacizumab application for treatment of mature corneal NV seemed to be a well-tolerated new treatment option to regress corneal NV. This may not only improve corneal transparency but also "preconditions" such a cornea for future keratoplasty.
EVALuna2:21110